Automatic calibration with robust control of a six DoF mechatronic system. (May 2016) - Chevalier, Amélie; Copot, Cosmin; Ionescu, Clara M.; De Keyser, Robin
Highlights: An automatic calibration procedure for a 6 DoF Stewart platform is proposed. Changes to the dynamics can be detected based on image processing techniques. The robust control method is tested by investigating highly changing dynamics. Abstract: This paper presents a robust control methodology incorporating an automatic calibration step to compensate dynamic variations in a 6 DoF mechatronic system. The application used to illustrate the efficacy of the proposed approach is the ball and plate system based on the Stewart platform. To emulate dynamic changes in the system, we make use of various types of balls, varying in mass, diameter and surface. An automatic calibration step is introduced to obtain a model based on the type of ball which is placed on the plate. Using a model-based tuning technique, an optimal proportional-differential (PD) controller is designed based on the previous calibration. The resulting controller is tested for robustness by changing the ball without changing the controller parameters. The results indicate that our setup is robust and performs well in the presence of significant changes.